A Novel Compact CPW LowPass Filter Integrating Periodic Triangle DGS Cells - Sghir, Elmahjouby; Errkik, Ahmed; Zbitou, Jamal; Tajmouati, A.; El Abdellaoui, Larbi; Latrach, Mohamed (Transactions on Engineering and Computing Sciences, 2017)
In this paper, we introduce a new periodic structure for CPW of a low pass filter based on the DGS technique with triangle slot cell forme. The proposed structure is a minuature low pass filter that exhibits low insertion loss in the passband, simple fabrication, and easy to integrate with microwave planar circuits. A Lowpass filter (LPF) has been designed with flat response at a selected frequency by cascading three DGS cells.